189: THE EFFECT OF COVID -19 ON THE NEW DIAGNOSIS OF ESOPHAGOGASTRIC CANCER IN THE UK: A SINGLE-CENTRE EXPERIENCE. (23rd April 2022) - Mcquillan, P; Ahmed, S; Hayes, N; Wahed, S; Navidi, M; Immanual, A; Phillips, A
Abstract: Background and aim: Covid-19 has had a devastating global impact and resulted in over 4.4 million directly attributed deaths. The UK entered lockdown in March 2020, redistributing its medical workforce and resources. Early estimations suggested at least 4700 extra cancer deaths at 5 years if there was a 3-month delay to surgery. Delays to diagnosis and treatment for esophagogastric (EG) cancers can be particularly detrimental to survival. The aim of this study is to assess the impact of Covid-19 on new cancer referrals to a centralised UK EG cancer centre, including presentation, decision making and treatment. Methods: Patients with EG cancer referred to a tertiary, high-volume centre between March 2019 and March 2021 were reviewed. Patients were stratified into Pre-covid (March 2019–March 2020) and Covid (March 2020–2021) cohorts. Number of new referrals, clinical stage, treatment decision, and time to treatment were compared for gastric adenocarcinoma (GA), esophagogastric-junction adenocarcinoma (EGJA), esophageal adenocarcinoma (EA) and esophageal SCC (ESCC). Results: There was an 11% reduction in new cancer referrals (485 vs 431). GA, EGJA and EA did not have significant change in treatment intent, although there was a significant increase in the decision for definitive non-surgical treatment of EA ( P = 0.046). GA and EA patients had a small, but significant increase in average clinical stage at presentation ( P < 0.05). There was no increase in time to treatment for GA, EGJA and EA. A significantly higher proportion of ESCC patients were given curative intent treatment in the Covid-19 cohort ( P = 0.0006) however, this was accompanied with an increased time to treatment (35.8 days vs 27.9 days P = 0.0198). Conclusion: This high-volume centre has seen a reduction in new cancer referrals since the first UK lockdown. This was associated with a small, but significant, increase in clinical stage of GA and EA at presentation. This may represent an early indication of excess esophagogastric cancer deaths due to the impact of Covid-19. This data also confirms initial results showing that oncological decisions were not compromised, although Covid-19 remains a dynamic challenge.